Infectious complications in patients receiving ticagrelor or clopidogrel before coronary artery bypass grafting. Issue 2 (February 2020) - ,; Perrotti, A.; Mariscalco, G.; Onorati, F.; Faggian, G.; Franzese, I.; Salsano, A.; Santini, F.; Ruggieri, V.G.; Maselli, D.; Nardella, S.; Santarpino, G.; et al.
Summary: The antiplatelet agent ticagrelor has recently been found to have bactericidal activity, demonstrated in vitro and in an in vivo mouse model, which warrants further clinical investigations. The aim of this study was to evaluate infectious complications after coronary artery bypass grafting in patients pre-operatively treated with ticagrelor or clopidogrel. In a multi-centre trial, all adult patients who were pre-operatively treated with ticagrelor or clopidogrel prior to isolated primary coronary artery bypass grafting were eligible. Propensity score matching was used. Outcome measures were any sternal wound infection, deep sternal wound infection, and any in-hospital use of postoperative antibiotics. Of 2311 patients who were included, 1293 (55.9%) received clopidogrel and 1018 (44.1%) ticagrelor pre-operatively. In both overall and propensity score matched analyses, ticagrelor was associated with a similar incidence of infectious complications compared to clopidogrel. Our findings do not support a clinically relevant bactericidal effect of ticagrelor in patients undergoing coronary artery bypass grafting.